Layer-specific genetic variation unlocks secondary metabolite diversity in long-lived clonal peppermint - Nestor Kippes; Meric C. Lieberman; Darrin Culp; Isabelle J. DeMarco; Helen T. Tsai; Kanae Masuda; Niccolò Terzaroli; Jordan Lopez; Robert G. Wilson; Luca Comai; Isabelle M. Henry (Proceedings of the National Academy of Sciences, 2026)
Mutations that arise in the shoot apical meristems can become fixed, but typically only in one of the meristem layers. Therefore, in long-lived, clonally propagated species, polymorphic genomes coexist in the form of periclinal chimeras. Given their evolutionary and economic impact, it is critical to understand the dynamics and phenotypic implications of layer-specific variation. Here, we γ-irradiated axillary buds from an elite peppermint clone and obtained 261 independent mutants carrying large indels. We produced a haplotype-aware, high-continuity assembly of this sterile allohexaploid and, using short-read sequencing, detected, on average, six large indels per mutant. Importantly, most of these mutants were periclinal chimeras: comparison of mutation frequency in root (derived solely from the L2/3 layer) and leaves (which contain cells from all three layers) demonstrated that the indels are confined to either the outer, L1-derived layer, or the inner L2/3 layers. We observed that the L1 layer was more often mutated, confirming that mutation rate in the shoot apical meristem is potentially optimized to each meristematic layer. To assess whether deletion of a single haplotype in a single meristematic layer could affect plant function, we characterized mutants under field conditions, detecting variation in secondary metabolite production. Two mutants produced an oil with very low (−)-menthol levels, associated with the loss of a single haplotype of the menthone-menthol reductase gene in the epidermal layer. These results highlight the evolutionary relevance of layer-specific genetic variation and present opportunities for improvement of clonally propagated crops that suffer from genetic diversity bottlenecks.